HUBUNGAN RIWAYAT KELUARGA DENGAN KEJADIAN HIPERTENSI DI RUMAH SAKIT PEKANBARU MEDICAL CENTER - Puspa Anggraini, Shelly; Humairah, Anugerah; Iqra Fikha, Idri; Jelsa Nabilah, Okta (Ensiklopedia of Journal, 2025)
Hypertension remains a condition whose symptoms and risk factors are not widely recognized and is classified as a degenerative disease. Genetic predisposition plays a significant role in the development of hypertension, both directly and indirectly. A study investigating risk factors for hypertension among communities living along the Siak River revealed that the majority of respondents diagnosed with hypertension (71.8%) had a family history of the disease. The presence of hypertension and cardiovascular disease within the family is associated with a 2- to 5-fold increased risk of developing hypertension. Genetic factors are therefore considered to contribute substantially to the risk of hypertension. Other studies have reported that 70–80% of essential hypertension cases are associated with a positive family history. This study aimed to examine the association between family history and the incidence of hypertension among outpatient hypertensive patients at Pekanbaru Medical Center Hospital. A quantitative analytic method with a cross-sectional design was employed, involving a total of 102 respondents. The study population comprised hypertensive outpatients aged 26 to 59 years attending the Internal Medicine Clinic. The results of statistical analysis indicated no significant association between family history and the incidence of hypertension, as demonstrated by a p-value of 0.253 (p > 0.05).Keywords      : Hypertension, Genetic factor.